THE ESTABLISHMENT OF RUMAH BUDAYA INDONESIA (RBI) IN SINGAPORE - Nabila Handayani (HI 16 UMY 130, 2016)
*130 Indonesia has much kind of diversities. As an archipelago country, there are a lot of cultures, languages, ethnic groups, beliefs, and so on. Although many different cultures and so on, Indonesia still become united, like one of the slogan which reads, â€œBhineka Tunggal Ikaâ€. The slogan itself told the people, although thereâ€™s a lot of a differences between the societies, they are still united. The cultural diversities itself was created because there are many kind of tribes and also ethnic groups in Indonesia. Not only because of the tribes and the ethnic groups, but also because of the geographic condition in Indonesia which have many islands that are separated. One of the heritages from Indonesia is the culture, such as traditional dances. Thereâ€™s lot of traditional dances and it depends on which part on Indonesia is that or where is it came from. As the nationâ€™s cultural heritage, traditional dances could become the identity of Indonesia and spread it through the international world. Traditional dances show the beautiful moves and also thereâ€™s a story behind the dances. The art of the dance itself could be the effective way to attract the international societies and reflect the peculiarities of Indonesia as a great nation uphold the diversity and also shows the value of the nation through friendship. This paper will analyze a program that is called as Rumah Budaya Indonesia in Singapore. It involves cultural diplomacy concept and also decision making-process as the instruments that is used to know the reasons why Indonesia built Rumah Budaya Indonesia in Singapore. First, this paper will explain the meaning of Indonesian cultures and why Indonesia needs to protect it.